Development of ecological liquid soap with coagulant properties for the purification of swine wastewater and its applicability to the community (Research, Society and Development, 2021)
Currently, the search for environmental technologies has been an important challenge for scientists, since the environment has been suffering countless impacts caused by the bad habits of humanity. Residual oil is one of the main solid wastes disposed of incorrectly, as it is difficult to handle, collect and treat. As a way to reduce the impact caused by this residue, the production of ecological soap has been discussed, from the residual oil and essential oils of Moringa oleifera, which have the capacity to facilitate the treatment of wastewater, since the plant has adsorbent characteristics and act as coagulating agents in water clarification, thus being able to replace aluminum salts, which are used in water treatment. In this sense, this work aims to develop and produce ecological soap with coagulant properties capable of helping in the purification of wastewater, reducing the cost of effluent treatment and also reducing the environmental impacts caused by the residual oil.